Efficient Green Solvent Extraction and Bioassay Studies of Favipiravir in Rat Dried Blood Spots Using Ionic Liquid-based Dispersive Liquid-liquid Microextraction (IL-DLLME) Coupled with HPLC-PDA: Application to Bioequivalence Studies - Rajashekhar, Kasturi; Naidu, Challa Gangu; Kumar, Chebolu Naga Sesha Sai Pavan; Ramachandra, Bondigalla (Current Pharmaceutical Analysis, 2024)
BackgroundFavipiravir is an antiviral drug having pyrazine group moiety. It is a reliable and an efficient green solvent, and a highly recoverable bio-sampling method is required for it. It is widely used in COVID-19 treatment for the prevention of the spread of viral infections in the body.ObjectiveThis proposed green solvent (ionic liquid)-based bioassay study aimed to quantify favipiravir in rat-dried blood spots using Dispersive Liquid-liquid Microextraction (IL-DLLME).MethodsThe proposed bioassay separation was achieved through an isocratic elution mode using a hybrid silica-based ODS column (250 × 4.6 mm; 5 µm), a column temperature of 25°C, an injection volume of 10 µL, a flow rate of 1.0 mL/min, and a detector wavelength set at 310 nm. The run time was less than 10 minutes. Mobile phase was delivered with acetonitrile, methanol, and 10 mM Na2HPO4 at pH 4.0 ± 0.5, (15: 20: 65, v/v/v). In a microtube, 50 mL of Ionic Liquid (IL), 500 µL of disperser ACN, 50 μL of 10% NaCl, and IS (20 ng mL-1) were added to perform the Dried Blood Spot (DBS) sample extraction methodology. The advantages of the proposed methodology have been found to include minimum hematocrit effect and an adequate blood volume for testing, easy transportation, and significant extraction recovery. The sample analysis has been carried out using HPLC-PDA with oseltamivir used as an internal standard.ResultsWe have investigated the important variables, i.e., salt concentration (10% NaCl, analyte recovery being higher) and disperser solvent [50μL of BMIHP plus 500 µL of ACN (v/v) yielding the highest recovery], in the extraction process. Extraction Recovery (ER) and Enrichment Factor (EF) were also evaluated using the IL-DLLME method. The calibration curve examined a range of 0.5-150 µg/mL, with a lower Limit of Quantification (LOQ) being 0.5 µg/mL in QC as well as calibration samples, respectively.ConclusionSignificant bioanalytical validation has been performed and all the parameters have been evaluated systematically as per bioanalytical method validation protocols, i.e., US FDA-2018 guidelines. The following analytical parameters have been covered: standard curve, limit of quantification, range, recovery, stability, accuracy, precision, sensitivity, ER, EF, and selectivity. The developed bioassay method has been successfully applied in the pharmacokinetic studies of rats and successfully applied in bulk drugs.
Keywords: pharmacokinetics